2013
DOI: 10.3171/2013.4.spine12961
|View full text |Cite
|
Sign up to set email alerts
|

Reliability in the location of hindlimb motor representations in Fischer-344 rats

Abstract: Object The purpose of the present study was to determine the feasibility of using a common laboratory rat strain for reliably locating cortical motor representations of the hindlimb. Methods Intracortical microstimulation techniques were used to derive detailed maps of the hindlimb motor representations in 6 adult Fischer-344 rats. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
(44 reference statements)
3
32
2
Order By: Relevance
“…Subsequently, current intensity was increased in 1 µA increments not exceeding 80 µA until a consistent movement was evoked with every stimulus train. The lowest stimulation current that evoked a visible and consistent joint displacement was defined as the movement threshold (Frost, Iliakova et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, current intensity was increased in 1 µA increments not exceeding 80 µA until a consistent movement was evoked with every stimulus train. The lowest stimulation current that evoked a visible and consistent joint displacement was defined as the movement threshold (Frost, Iliakova et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…2628 Two recent neurophysiological studies using ICMS techniques reported that the hindlimb motor area in rodents was, on average, 1–3.25 mm and 0.75–2.75 mm lateral to midline in rats 27 (Figure 2) and mice, 29 respectively. Following traumatic brain injury in rats, ICMS stimulation in the MC contralateral to the injury (the non-injured MC) elicited more ipsilateral hindlimb movements than sham operated (uninjured rats).…”
Section: Interhemispheric Communication Between the Leg Motor Corticamentioning
confidence: 98%
“…A craniectomy was performed over the motor cortex. The general location of the craniectomy was guided by previous motor mapping studies in the rat (Frost et al, 2013;Frost et al, 2015). The dura over the cranial opening was incised and the opening was filled with warm, medical grade, sterile, silicone oil (50% Medical Silicone Fluid 12,500, 50% MDM Silicone Fluid 1000, Applied Silicone Corp., Santa Paula, CA) to prevent desiccation during the experiment.…”
Section: Hfrugmentioning
confidence: 99%